Hacia el cambio... : 100 días de gobierno / PSOE ; prólogo de Ramón Rubial - Rubial, Ramón (1906-1999) González Márquez, Felipe (1942-) Guerra, Alfonso (1940-) Boyer, MiguelLedesma Bartret, FernandoMorán, Fernando (1926-) Quadra-Salcedo y Fernández del Castillo, Tomás de laAlmunia, Joaquín (1948-)
Contiene entrevistas con Felipe González, Alfonso Guerra, Miguel Boyer, Fernando Ledesma, Fernando Morán, Tomás de la Quadra-Salcedo y Joaquín Almunia